2023
DOI: 10.1371/journal.pone.0278020
|View full text |Cite
|
Sign up to set email alerts
|

Understanding accelerators to improve SDG-related outcomes for adolescents—An investigation into the nature and quantum of additive effects of protective factors to guide policy making

Abstract: Recent evidence has shown support for the United Nations Development Programme (UNDP) accelerator concept, which highlights the need to identify interventions or programmatic areas that can affect multiple sustainable development goals (SDGs) at once to boost their achievement. These data have also clearly shown enhanced effects when interventions are used in combination, above and beyond the effect of single interventions. However, detailed knowledge is now required on optimum combinations and relative gain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, while our study showed that a more diverse/richer resource combination was associated with greater mental health, it did not suggest an optimal number of multisystemic resources. Research investigating the usefulness of the United Nations Development Program's concept of accelerators (PFPs that accelerate the realization of a sustainable development goal) has prompted interest in an optimal number of resources (Sherr et al, 2023). In South Africa, for example, the probability of no depression in a sample of adolescents from resource-constrained communities in the Eastern Cape increased from 65.5% to 83.9% with access to a single PFP (community-based services).…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Moreover, while our study showed that a more diverse/richer resource combination was associated with greater mental health, it did not suggest an optimal number of multisystemic resources. Research investigating the usefulness of the United Nations Development Program's concept of accelerators (PFPs that accelerate the realization of a sustainable development goal) has prompted interest in an optimal number of resources (Sherr et al, 2023). In South Africa, for example, the probability of no depression in a sample of adolescents from resource-constrained communities in the Eastern Cape increased from 65.5% to 83.9% with access to a single PFP (community-based services).…”
Section: Implications For Research and Practicementioning
confidence: 99%